1997
DOI: 10.1109/78.564174
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Zak transforms, polyphase transforms, and applications

Abstract: Abstract-We consider three different versions of the Zak transform (ZT) for discrete-time signals, namely, the discretetime ZT, the polyphase transform, and a cyclic discrete ZT. In particular, we show that the extension of the discrete-time ZT to the complex z-plane results in the polyphase transform, an important and well-known concept in multirate signal processing and filter bank theory.We discuss fundamental properties, relations, and transform pairs of the three discrete ZT versions, and we summarize app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 54 publications
0
84
0
Order By: Relevance
“…We consider a DFT FB (see Section VII-A) with channels and a 192-tap lowpass analysis prototype filter . The simulation results were obtained by performing all calculations within the framework of cyclic DFT FB's (cyclic Weyl-Heisenberg frames) [39] with period 192. The dual windows and the frame bounds we obtained are, hence, approximations to the true (i.e., noncyclic) dual windows and frame bounds.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider a DFT FB (see Section VII-A) with channels and a 192-tap lowpass analysis prototype filter . The simulation results were obtained by performing all calculations within the framework of cyclic DFT FB's (cyclic Weyl-Heisenberg frames) [39] with period 192. The dual windows and the frame bounds we obtained are, hence, approximations to the true (i.e., noncyclic) dual windows and frame bounds.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Proof: Using (6), it can easily be shown that , where : denotes the polyphase transform (Zak transform) operator, i.e., the operator mapping a signal to the polyphase domain with . Since is a unitary transformation [39], it follows that and are unitarily equivalent. Therefore, and have the same eigenvalues [44].…”
Section: A Matrix Representation Of the Frame Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…) and critical sampling, the Gabor frame operator can conveniently be expressed using the Zak transform (ZT) [6], [2], [14], [15]. For , the ZT of a signal is defined as (7) In this letter, we will be only concerned with the case and .…”
Section: B the Zak Transformmentioning
confidence: 99%